Structural Modeling of the Mediating Role of Self-Compassion in the Relationship Between Family Cohesion and Sexual Satisfaction with Marital Adjustment Among Married Students of Islamic Azad University, Rasht - Esmaili, Mehrab; Majidi, Seyed Ali (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the mediating role of self-compassion in the relationship between family cohesion and sexual satisfaction with marital adjustment among married university students.Methods and Materials: This study employed an applied, descriptive-correlational design using structural equation modeling (SEM). The statistical population consisted of all married students of Islamic Azad University, Rasht Branch, during the 2024–2025 academic year (N = 1,140), from whom 290 participants were selected through proportional stratified random sampling based on the Morgan table. Data were collected using Samani’s Family Cohesion Questionnaire, Larson’s Sexual Satisfaction Questionnaire, Neff’s Self-Compassion Scale, and Spanier’s Marital Adjustment Scale. The validity and reliability of the instruments had been confirmed in previous studies. Data analysis was conducted using SPSS version 21 for descriptive statistics and SmartPLS version 3 for inferential analysis.Findings: The results indicated that family cohesion and sexual satisfaction had significant direct effects on marital adjustment. Both variables also showed significant positive relationships with self-compassion, which in turn significantly predicted marital adjustment. Structural equation modeling revealed that self-compassion played a significant mediating role in the relationship between family cohesion and marital adjustment, as well as between sexual satisfaction and marital adjustment. The measurement and structural models demonstrated acceptable reliability and validity, with factor loadings exceeding 0.50, AVE values above 0.50, and satisfactory discriminant validity based on the Fornell–Larcker criterion. Additionally, the structural model exhibited adequate explanatory power (R² values of 0.527 for self-compassion and 0.732 for marital adjustment) and strong overall model fit (GOF = 0.620).Conclusion: Enhancing family cohesion and sexual satisfaction, along with fostering self-compassion, may contribute to improved marital functioning and relational stability among married individuals.